Determinan Niat Investasi Green Sukuk pada Investor di DKI Jakarta: Penerapan Theory of Planned Behaviour - Ismail (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study aims to investigate the intention behavior of investors in DKI Jakarta when investing in green sukuk, using variables supporting environmental protection (SEP), the Theory of Planned Behavior (TPB) model, and Islamic financial literacy as determining factors. TPB is a research model consisting of attitude, subjective norm, and perceived behavioral control variables. SEP and Islamic financial literacy variables are included as factors that can also influence an individual's decision to invest. The research method used is quantitative, employing survey techniques and questionnaires as data collection tools. The research is conducted in the DKI Jakarta area, with respondents who are residents of DKI Jakarta. Hypothesis testing is done using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with multiple regression analysis. The results of hypothesis testing indicate that attitudes towards behavior, subjective norms, perceived behavioral control, and support for environmental protection significantly influence the intention to invest in green sukuk. However, Islamic financial literacy does not have a significant influence on investment intention.